Epilepsy and ultra-structural heart changes: The role of catecholaminergic toxicity and myocardial fibrosis. What can we learn from cardiology?. (October 2019) - Fialho, Guilherme L.; Wolf, Peter; Walz, Roger; Lin, Katia
Highlights: Patients with epilepsy (PWE) have an increased risk for sudden unexpected death. Seizures promote autonomic dysfunction and higher sympathetic drive. Autonomic dysfunction is related to catecholaminergic toxicity and cardiac fibrosis. Ultra-structure fibrosis leads to arrhythmia and a heart failure-like phenotype in PWE. Translational lessons from cardiac models are used to support these considerations. Abstract: In this article, we explore the interaction of brain and heart in patients with epilepsy (PWE), focusing on new insights into possible pathways from epilepsy, catecholaminergic toxicity, subtle cardiac changes and sudden death. Initial evidence and biological plausibility point to an interaction between autonomic dysfunction, higher sympathetic drive, myocardial catecholaminergic toxicity and cardiac fibrosis resulting in subtle myocardial changes in structure, function, arrhythmogenesis and/or a heart failure-like phenotype in PWE. Non invasive imaging and biomarkers of cardiac injury and fibrosis are emerging as possible diagnostic tools to better stratify the risk of such individuals. Translational lessons from cardiac models of disease and ultra-structural lesions are used to support these considerations.